Renal echo-3D and microalbuminuria in children of diabetic mothers: a preliminary study. (10th April 2013) - Cappuccini, B.; Torlone, E.; Ferri, C.; Arnone, S.; Troiani, S.; Bini, V.; Bellomo, G.; Barboni, G.; Di Renzo, G.
Abstract : Maternal diabetes has assumed epidemic relevance in recent years and animal studies have provided some evidence that it may cause abnormalities in renal development and a reduction in nephron endowment in the offspring; however, human data are lacking. The renal cortex contains ∼95% of the glomeruli and its volume could be taken as a surrogate measure of glomerular number; based on this assumption, we measured renal cortex volume and in addition, microalbuminuria in a homogeneous sample of 42 children of diabetic (pregestational, n = 13, and gestational, n = 29) mothers, compared with 21 healthy children born of non-diabetic mothers. The offspring of diabetic mothers showed a significant reduction of renal cortex volume and higher albumin excretion compared with controls, possibly attributable to a reduction in the number of nephrons and the difference was statistically significant ( P < 0.001). Although further studies on a larger sample are necessary, our preliminary findings suggest that maternal diabetes may affect renal development with sequelae later in life, requiring closer monitoring and follow-up. Furthermore, the importance of strict maternal diabetes management and control must be emphasized.